A Digital Transformation Framework for Pesantren: Integrating Technology and Sharia Principles in Startup Development - Mufidatul Islamiyah (Al-Fiqh: Journal of Contemporary Islamic Law, 2025)
This study examines how Islamic boarding schools implement digital transformation to develop Sharia-compliant startup ecosystems that promote institutional economic independence. The research is significant as pesantren in Indonesia face increasing demands to remain economically sustainable while preserving religious identity in the digital era. Using a qualitative case study approach, the study focuses on Pesantren and its business units. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using thematic coding. The findings reveal three major outcomes: a phased digital transformation model that integrates religious authority with professional governance; the embedding of Sharia principles within digital financial and operational systems; and the development of an ecosystem-based economic structure that strengthens institutional self-reliance. The study concludes that digital transformation in pesantren can function as a culturally anchored modernization strategy that enhances transparency, scalability, and sustainability without compromising doctrinal values. It recommends that Islamic educational institutions adopt phased, Sharia-embedded digital strategies and strengthen ecosystem-based entrepreneurship to achieve long-term economic resilience.